2016
DOI: 10.1016/j.hydromet.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Processing of rare earth phosphate concentrates: A comparative study of pre-leaching with perchloric, hydrochloric, nitric and phosphoric acids and deportment of minor/major elements

Abstract: Phosphate rocks such as fluorapatite often contain significant amounts of rare earth minerals and considered as rare earth ores. They can be processed to produce phosphoric acid as well as rare earth metals. The mineralization, however, is commonly associated with other rare earth minerals such as monazite ((Ce,La,Th,Nd,Y)PO 4), florencite ((La,Ce)Al 3 (PO 4) 2 (OH) 6), xenotime (YPO 4) and cheralite ((Ca,Ce)(Th,Ce)(PO 4) 2). The treatment of fluorapatite for rare earth extraction commonly requires a pre-leach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The REE content of the phosphate ore residue determined from XRF is shown in Table 2 (the full XRF results are provided in the Supporting Information). and H3PO4 and concluded that the dissolution of REEs in H3PO4 was lower compared to the other three acids [24]. H2SO4 allowed partial leaching of REEs from the phosphate ore residue.…”
Section: Liquid / Liquid Extractionmentioning
confidence: 97%
See 1 more Smart Citation
“…The REE content of the phosphate ore residue determined from XRF is shown in Table 2 (the full XRF results are provided in the Supporting Information). and H3PO4 and concluded that the dissolution of REEs in H3PO4 was lower compared to the other three acids [24]. H2SO4 allowed partial leaching of REEs from the phosphate ore residue.…”
Section: Liquid / Liquid Extractionmentioning
confidence: 97%
“…Furthermore, the huge amount of apatite ores on Earth (the world phosphate rock production is estimated to be more than 250 million tons per year [15]) makes this material a promising alternative source for extraction of REEs [24,25]. It is noteworthy, however, that extraction of REEs from apatite has not been extensively studied compared to other main minerals such as monazite, bastnasite and xenotime [9].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphoric acid is produced from the dissolved apatite, which still contains dissolved Ca. The dissolved Ca could be precipitated as gypsum (CaSO 4 .2H 2 O) by the addition of a stoichiometric amount of sulphuric acid (Stone et al, 2016). Process residue from the pre-leach stage is subjected to acid baking at elevated temperature.…”
Section: Selection Of An Appropriate Leaching Methods For Light Reesmentioning
confidence: 99%
“…The Eh-pH diagrams for the system Th-RE-(PO 4 )-(SO 4 )-H 2 O at 25°C and different concentrations of metal ions (10 -3 , 10 -1 mol/L), phosphate (10 -3 mol/L) and sulfate (10 -2 , 10 -1 and 1 mol/L) published by Kim and Osseo-Asare (2012) predict the stability regions for a variety of species relevant to the hydrometallurgical processing of monazite via sulfuric acid baking and leaching. The solution composition and measured solubility of rare earths, thorium and uranium in sulfuric-phosphoric solutions produced after acid baking/leaching or pre-leaching of rare-earth concentrates provide useful information on solid phases and complex species of these metal ions relevant to baking, leaching and precipitation (Bandara and Senanayake, 2015;Bandara and Senanayake, 2019;Bandara et al, 2018;Demol et al, 2018;Senanayake et al, 2016;Stone et al, 2016).…”
Section: Type Of Saltmentioning
confidence: 99%